Rooted together: fostering connection through archaeobotany - Marvin Demicoli; Sadie Watson; Kate Faccia (Vegetation History and Archaeobotany, 2026)

Genome‐Wide DNA Methylation Patterns Predict Age in the Zebra Shark ( Stegostoma tigrinum ) and Provide Insight Into the Evolution of Vertebrate Aging - Samantha L. Bock; Kady Lyons; Lei Yang; Jennifer Wyffels; Lance Adams; Nienke Klerks; Aaron Jeskie; Ellen Leever; Taylor Hartl; Javier Almunia; Dan Peterson; Ana Ferreira; et al. (Molecular Ecology, 2026)
Epigenomic changes are a hallmark of aging, and DNA methylation (DNAm) has emerged as the most reliable molecular marker of an individual's age. Genome‐wide patterns of age‐associated hypo‐ and hypermethylation have been applied to generate predictive models (i.e., “epigenetic clocks”) capable of estimating chronological age in an increasingly diverse set of species including many mammals, a few birds, a reptile, and several bony fishes. Elasmobranchs (sharks, skates, and rays) are underrepresented in comparative investigations of epigenetic aging despite exhibiting exceptional life history variation, occupying a key basal position in the vertebrate phylogeny, and encompassing a large proportion of threatened species lacking accurate, non‐lethal age determination methods. Here, we characterize epigenome‐wide aging signals in the zebra shark ( Stegostoma tigrinum ), a long‐lived elasmobranch of conservation concern, from whole‐genome enzymatic methyl‐sequencing of whole blood. Using a cohort of 51 known‐age aquarium‐bred individuals, we develop several epigenetic clock models capable of predicting chronological age with a median absolute error of 1.03–1.99 years (3.32%–6.42% of lifespan) based on the methylation status of as few as ten cytosines. We further apply our models to 19 individuals of unknown age originating from the wild. By profiling the broader age‐associated methylome we demonstrate that these patterns not only predict age with high accuracy but also exhibit striking similarities in their genomic distributions to those observed in mammals pointing to conservation of the processes underlying epigenetic aging across vertebrates.

Oral L-Dopa Disrupts Behavioral Self-Control in Male Fighting Fish (Betta splendens) - Andrew Velkey; Kate Watson; Nathan White; Abigail Agi; Grace Doebler-Alligood; Isabella Tilmont; Brook Williams Sweeten; Kaitlyn Kinslow (Fishes, 2025)
In their natural habitat, male Betta splendens are territorial resource defenders, whereas females are non-territorial opportunistic foragers. This ecological difference suggests that males may be more capable of delaying gratification for food rewards. The present study examined impulsive choice in Betta splendens through two experiments comparing subjects’ choices between a Smaller-Sooner (SS) reward (1 pellet immediately) and a Larger-Later (LL) reward (3 pellets after 15 s). In Experiment I, the choice distributions of males were more likely to stabilize on the LL option over the SS option, whereas females’ choice distributions were equally likely to stabilize on either option. These findings indicate that most males demonstrated spontaneous behavioral self-control without specialized training, while females were collectively indifferent. Experiment II investigated whether dopamine modulates this behavior by administering oral L-Dopa (60 mg/kg) to males before trials. Using the same procedures, only 30% of L-Dopa-treated males’ choice distributions stabilized on the LL reward, while 70% of experimental males’ choice distributions stabilized on the SS option; the choice distributions of control males were equally likely to stabilize on either reward. These results suggest that elevated dopaminergic activity increases impulsive choice in male Betta splendens. Future studies should examine dopamine agonists and antagonists, as well as female responses, to further clarify dopamine’s role in reward valuation and behavioral self-control in Betta splendens.

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Comprehensive Characterisation of the RFC1 Repeat in an Australian Cohort - Kayli C. Davies; Haloom Rafehi; Liam G. Fearnley; Penny Snell; Greta Gillies; Tess A. Field; Gábor M. Halmágyi; Kishore R. Kumar; Kate Pope; Renee Smyth; Susan E. Tomlinson; Stephen Tisch; et al. (The Cerebellum, 2025)

Laboratory investigations into alternative baits for the channeled whelk (Busycotypus canaliculatus) fishery - Mary Kate Munley; Elizabeth A. Fairchild; Steven H. Jury; Winsor H. Watson; Shelley A. Edmundson (Fisheries Research, 2024)

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

Development of a Seafloor Community Classification for the New Zealand Region Using a Gradient Forest Approach - Fabrice Stephenson; Ashley A. Rowden; Tom Brough; Grady Petersen; Richard H. Bulmer; John R. Leathwick; Andrew M. Lohrer; Joanne I. Ellis; David A. Bowden; Shane W. Geange; Greig A. Funnell; Debbie J. Freeman; et al. (Frontiers in Marine Science, 2022)
To support ongoing marine spatial planning in New Zealand, a numerical environmental classification using Gradient Forest models was developed using a broad suite of biotic and high-resolution environmental predictor variables. Gradient Forest modeling uses species distribution data to control the selection, weighting and transformation of environmental predictors to maximise their correlation with species compositional turnover. A total of 630,997 records (39,766 unique locations) of 1,716 taxa living on or near the seafloor were used to inform the transformation of 20 gridded environmental variables to represent spatial patterns of compositional turnover in four biotic groups and the overall seafloor community. Compositional turnover of the overall community was classified using a hierarchical procedure to define groups at different levels of classification detail. The 75-group level classification was assessed as representing the highest number of groups that captured the majority of the variation across the New Zealand marine environment. We refer to this classification as the New Zealand “Seafloor Community Classification” (SCC). Associated uncertainty estimates of compositional turnover for each of the biotic groups and overall community were also produced, and an added measure of uncertainty – coverage of the environmental space – was developed to further highlight geographic areas where predictions may be less certain owing to low sampling effort. Environmental differences among the deep-water New Zealand SCC groups were relatively muted, but greater environmental differences were evident among groups at intermediate depths in line with well-defined oceanographic patterns observed in New Zealand’s oceans. Environmental differences became even more pronounced at shallow depths, where variation in more localised environmental conditions such as productivity, seafloor topography, seabed disturbance and tidal currents were important differentiating factors. Environmental similarities in New Zealand SCC groups were mirrored by their biological compositions. The New Zealand SCC is a significant advance on previous numerical classifications and includes a substantially wider range of biological and environmental data than has been attempted previously. The classification is critically appraised and considerations for use in spatial management are discussed.

Corrigendum: Seasonal Dynamics in Dissolved Organic Matter, Hydrogen Peroxide, and Cyanobacterial Blooms in Lake Erie - Rose M. Cory; Timothy W. Davis; Gregory J. Dick; Tom Johengen; Vincent J. Denef; Michelle Berry; Sarah E. Page; Susan B. Watson; Kate Yuhas; George W. Kling (Frontiers in Marine Science, 2017)

Seasonal Dynamics in Dissolved Organic Matter, Hydrogen Peroxide, and Cyanobacterial Blooms in Lake Erie - Rose M. Cory; Timothy W. Davis; Gregory J. Dick; Thomas Johengen; Vincent J. Denef; Michelle A. Berry; Sarah E. Page; Susan B. Watson; Kate Yuhas; George W. Kling (Frontiers in Marine Science, 2016)

Regulation of spirocyst discharge in the model sea anemone, Nematostella vectensis - Sherry L. Krayesky; Janna L. Mahoney; Katherine M. Kinler; Stacey Peltier; Warnesha Calais; Kate Allaire; Glen M. Watson (Marine Biology, 2010)

Effect of aspirin on hypothalamic–pituitary–adrenal function and on neuropsychological performance in healthy adults: a pilot study - Stuart Watson; Kate Horton; Samantha Bulmer; Jane Carlile; Ciaran Corcoran; Peter Gallagher; I. Nicol Ferrier (Psychopharmacology, 2009)

On the Role of Basic Residues in Adapting the Reaction Centre–LH1 Complex for Growth at Elevated Temperatures in Purple Bacteria - Ashley J. Watson; Arwel V. Hughes; Paul K. Fyfe; Marion C. Wakeham; Kate Holden-Dye; Peter Heathcote; Michael R. Jones (Photosynthesis Research, 2005)